2019
DOI: 10.5005/jp-journals-10005-1628
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Esthetic Defects in Anterior Teeth on the Emotional and Social Well-being of Children: A Survey

Abstract: ObjectivesThis study aimed to determine whether imperfections in the anterior dentition affect the emotional and/or social well being of school going children in Amritsar district of Punjab, India.MethodsA total of 2582 children between the ages 10 and 15 years of both genders were examined. Of these, 528 children with esthetic imperfections were asked a series of questions to assess their emotional and social disposition, with respect to children with no esthetic defects.ResultsFemales were more shy if they d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
(25 reference statements)
0
6
0
2
Order By: Relevance
“…Identifying populations that are a greater risk of oral conditions like enamel defects is important to ensure the provision of appropriate care, and the development of public health policies and preventative schemes. Developmental defects of enamel can cause premature tooth loss, hypersensitivity, and poor aesthetics 3,20,21 . All of the aforementioned can negatively impact an individual's quality of life and masticatory function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying populations that are a greater risk of oral conditions like enamel defects is important to ensure the provision of appropriate care, and the development of public health policies and preventative schemes. Developmental defects of enamel can cause premature tooth loss, hypersensitivity, and poor aesthetics 3,20,21 . All of the aforementioned can negatively impact an individual's quality of life and masticatory function.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical disturbances of enamel quantity and quality increase the risk of dental caries, hypersensitivity, and premature tooth wear 2 . They can also pose a considerable aesthetic concern for patients 3 . Dental fear and anxiety as well as dental behavioural problems as a consequence of DDEs have been reported 1 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that 20-40% of adolescents are affected, with the phenome non being more prevalent in females. [8][9][10][11] Bullying has been associated with malocclusion, mainly when both the mandible and the maxilla are affected. 12 Children with class III malocclusion are more likely to experi ence bullying as compared to those with mild or absent malocclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Estos estudios han demostrado que la CPI y la CPI-S generan un impacto negativo en la calidad de vida relacionada a salud bucal en los niños y en sus familias. [4][5] La presencia de caries en niños está relacionada con una serie de factores biológicos, sociales y comportamentales; [6][7][8][9] también pueden producirse alteraciones del desarrollo infantil temprano (lenguaje, psicomotor, cognitivo, social y emocional), 10 problemas estéticos, 11 dificultades para la alimentación, [12][13][14] aparición de maloclusiones y hábitos orales [15][16][17][18] consumo azúcar, 19 además de repercusiones médicas-odontologicas, 20 financieras, 21,22 baja escolaridad de los padres, 23 bajo nivel socioeconómico, 24,25 hábitos alimentarios 26,27 e higiénicos inadecuados 28 entre otros.…”
Section: Introductionunclassified